(untitled) (Revista horizonte, 2016)
Physical exercise has shown positive effects on postural balance of the elderly. Objective: The objective of this study was to analyze the characteristics of postural balance of elderly women that practice swimming and entertaining dance. Method: 50 elderly women were recruited, divided into 2 groups of 25 people (swimming with age 64.3 ± 2.7; weight 66.7 ± 13.1; height 1.56 ± 0.1 and entertaining dance with age 64.7 ± 3.3; weight 66.9 ± 13.1; height 1.56 ± 0.1). People were selected under a criterion non probabilistic for convenience. A non-experimental, descriptive comparative design was adopted. To analyze were consider the characteristics of postural balance of medium speed, area of shift, energy in terms of closed eyes and front view and also the Romberg index through posturography. Result: the result shown less value of medium speed, area and energy to the group of elderly, who attend to dance classes with significant differences. Conclusion: to conclude, elderly who practice entertaining dance shown better conditions than elderly who practice swimming, with no significant differences according to the values of Romberg.